Resonant Reflection From Cylindrical Grating-Waveguide Under Holistic Excitation - Erieta Katerina Koussi; Hugo Bruhier; M. A. Usuga Higuita; Isabelle Verrier; Colette Veillas; Thomas Kampfe; Stephanie Reynaud; Nicolas Crespo-Monteiro; Olivier Parriaux; Yves Jourlin (IEEE Photonics Journal)
The phenomenon of resonant reflection from a grating-coupled waveguide mode is conceptually, technologically, and experimentally transposed from a planar corrugated waveguide structure under plane wave excitation to a circularly symmetrical waveguide at the inner wall of a tube under cylindrical wave excitation. The mode coupling element is an azimuthally periodic wall corrugation having an integer number of lines parallel to the tube axis. The grating is defined by diffractive coordinate transform of a radial grating phase-mask transverse to the tube axis under axial beam exposure onto a photoresist-coated TiO2 sol-gel wall-waveguide. The holistic excitation of a waveguide mode is achieved by transforming a broad spectrum, centered axial incident beam into a cylindrical wave by a centered, 90° apex reflective cone. The expected resonantly reflected cylindrical wave at the mode-coupling wavelength is in turn transformed back into an axial beam by the cone. TE resonant reflection is demonstrated experimentally.